Australian species of spore-feeding Thysanoptera in the genera Carientothrips and Nesothrips (Thysanoptera: Idolothripinae) - Eow, Li-Xin; Mound, Laurence A; Tree, Desley J; Cameron, Stephen L (Zootaxa, 2014)
The species from Australia in the genera Carientothrips and Nesothrips are reviewed and an illustrated key is provided. Carientothrips is distinguished based on the unusual form of the maxillary palps. Two species, badius Hood comb.n. and capricornis Mound comb.n., are transferred to Nesothrips from Carientothrips; and Nesothrips melinus Mound syn.n. is synonymised with Carientothrips miskoi Mound. In Carientothrips the following six new species are described: alienatus sp.n., calami sp.n., horni sp.n., palumai sp.n., snowi sp.n., tasmanica sp.n.; while flavitibia Moulton stat.rev. is recalled from synonymy with C. mjobergi (Karny). In Nesothrips four new species are described: barrowi sp.n., brigalowi sp.n., coorongi sp.n., rossi sp.n.; while rhizophorae (Girault) syn.n. is placed as a synonym of minor Bagnall.